The association between manganese exposure with cardiovascular disease in older adults: NHANES 2011–2018. Issue 11 (19th September 2021) - Xiao, Shengjue; Zhou, Yufei; Liu, Tao; Hu, Yue; Wu, Qi; Pan, Qinyuan; Wang, Xiaotong; Liu, Ailin; Liu, Jie; Zhu, Hong; Yin, Ting; Pan, Defeng
Abstract: The aim of the current study was to explore possible connections between manganese exposure and the prevalence of cardiovascular disease (CVD) in older US adults. The relationship between serum manganese levels and CVD was explored in 2427 people aged 60 years and over using data from the National Health and Nutrition Examination Survey (NHANES) (2011–2018). Multivariate linear regression analysis was performed to investigate associations between CVD risk factors and serum manganese concentration. The relationship between manganese levels and the prevalence of CVD was probed using generalized linear models and restricted cubic spline curves. Stratified subgroup analysis was subsequently constructed to rule out spurious interactions between variables and manganese. Compared with the lowest quartile, the modified odds ratios (ORs) with 95% confidence intervals (CIs) for CVD prevalence across the manganese quartiles were 0.71 (OR: 0.51; CI: 1.00), 0.70 (0.50, 0.99), and 0.49 (0.34, 0.72). In the full adjusted model, a prominent negative relationship was observed between serum manganese concentration and CVD. A restricted cubic spline curve was used to show a nonlinear negative relationship between manganese concentration and CVD. In summary, manganese levels are negatively correlated with the risk of CVD in a nation-wide study of older US adults.